2018
DOI: 10.1007/s00125-018-4639-6
|View full text |Cite
|
Sign up to set email alerts
|

Advances in drug discovery for human beta cell regeneration

Abstract: The numbers of insulin-secreting pancreatic beta cells are reduced in people with type 1 and type 2 diabetes. Driving beta cell regeneration in the pancreases of people with diabetes would be an attractive approach to reversing diabetes. While adult human beta cells have long been believed to be terminally differentiated and, therefore, irreversibly quiescent, it has become clear over recent years that this is not true. More specifically, both candidate and unbiased high-throughput screen approaches have revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 61 publications
(116 reference statements)
1
21
0
1
Order By: Relevance
“…Future work is indicated to determine if such a population of cells could be utilized for strategies aiming to regenerate β cell mass in individuals with undetectable serum C-peptide. 33 We also found that unmethylated INS DNA levels were actually reduced among subjects with one or two high-risk HLA-DRB1 alleles compared with subjects without high-risk HLA alleles. This finding could potentially reflect heterogeneity in the T1D course, with high- Consistent with prior work, we also detected increased methylated INS DNA levels in T1D subjects.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Future work is indicated to determine if such a population of cells could be utilized for strategies aiming to regenerate β cell mass in individuals with undetectable serum C-peptide. 33 We also found that unmethylated INS DNA levels were actually reduced among subjects with one or two high-risk HLA-DRB1 alleles compared with subjects without high-risk HLA alleles. This finding could potentially reflect heterogeneity in the T1D course, with high- Consistent with prior work, we also detected increased methylated INS DNA levels in T1D subjects.…”
Section: Resultssupporting
confidence: 51%
“…Along these lines, our findings could also reflect a relative predominance of a persistent dysfunctional β cell subpopulation that is relatively resistant to autoimmune destruction. Future work is indicated to determine if such a population of cells could be utilized for strategies aiming to regenerate β cell mass in individuals with undetectable serum C‐peptide …”
Section: Discussionmentioning
confidence: 99%
“…Regeneration of β-cell is another process that may account for recovery β-cell mass after remission, and some drugs have been reported to have such proliferative effects. However, evidence of β-cell replication or proliferation is lacking in adult humans [ 108 , 200 , 201 ].…”
Section: Mechanisms Of Remission Of T2dm After Weight Lossmentioning
confidence: 99%
“…This could also have a beneficial influence on pancreatic architecture given the established positive effects of GIP on beta‐cell growth and survival 49‐51 . However, it should also be noted that actual proliferation rates of adult pancreatic beta‐cells are low 52 . Indeed, corresponding observations on positive beta‐cell growth effects of approved glucagon‐like peptide‐1 mimetics in animal models of diabetes, are only evidenced in human islets in vitro to date 53 .…”
Section: Discussionmentioning
confidence: 99%